2005
DOI: 10.1523/jneurosci.5104-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pincher-Mediated Macroendocytosis Underlies Retrograde Signaling by Neurotrophin Receptors

Abstract: Retrograde signaling by neurotrophins is crucial for regulating neuronal phenotype and survival. The mechanism responsible for retrograde signaling has been elusive, because the molecular entities that propagate Trk receptor tyrosine kinase signals from the nerve terminal to the soma have not been defined. Here, we show that the membrane trafficking protein Pincher defines the primary pathway responsible for neurotrophin retrograde signaling in neurons. By both immunofluorescence confocal and immunoelectron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 46 publications
4
146
0
Order By: Relevance
“…In this study, internalized Trk-endosomes retain association with rab5, a small GTPase involved in the formation of the early endosome (Bucci et al 1992), which prevents maturation to rab7-positive late endosomes and degradation through the lysosomal pathway. Furthermore, the retention of rab5-positive endosomes promotes sustained NGF-stimulated signaling (Valdez et al 2005(Valdez et al , 2007. These data are consistent with another study performed on peripheral sensory neurons in which retrograde signaling of TrkA occurred in early endosomes (Delcroix et al 2003).…”
Section: Internalization and Retrograde Signalingsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, internalized Trk-endosomes retain association with rab5, a small GTPase involved in the formation of the early endosome (Bucci et al 1992), which prevents maturation to rab7-positive late endosomes and degradation through the lysosomal pathway. Furthermore, the retention of rab5-positive endosomes promotes sustained NGF-stimulated signaling (Valdez et al 2005(Valdez et al , 2007. These data are consistent with another study performed on peripheral sensory neurons in which retrograde signaling of TrkA occurred in early endosomes (Delcroix et al 2003).…”
Section: Internalization and Retrograde Signalingsupporting
confidence: 89%
“…Various reports have demonstrated that retrograde signaling of Trk is required for survival of peripheral and central neurons in culture through the activation of ERK5, phosphorylation of the cAMP response element-binding protein, and the consequent initiation of gene transcription (Ye et al 2003;Heerssen et al 2004;Valdez et al 2005). Furthermore, retrograde signaling from dendrites of hippocampal neurons has been linked to long-term potentiation (Patterson et al 2001).…”
Section: Internalization and Retrograde Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…One set of hypotheses for retrograde axonal transport of NGF states that NGF and its signaling proteins are transported in complex vesicles such as multivesicular bodies, lysosomes, or macropinosomes (8,20,36). To examine the endocytic compartment(s) that immediate the retrograde transport of QD-NGF, we took advantage of the fact that QD has an electron dense core that can be visualized under electron microscopy (EM) (37).…”
Section: Most Qd-ngf Is Transported In Axons In Small 50-to 150-nm Vementioning
confidence: 99%
“…The signaling endosome model proposes that upon ligand binding and activation, Trk receptors at the distal axon are internalized via clathrin-mediated [12][13][14] or pincher-dependent endocytosis [15,16]. The resultant vesicles containing the ligand-receptor complex are retrogradely transported to the cell body in order to mediate a survival response [3,[7][8][9][10][11]17, 18].…”
Section: Retrograde Axonal Transport Mechanismsmentioning
confidence: 99%